Hubungan Karakteristik Ibu Dengan Status Gizi Anak Balita Yang Memiliki Jamkesmas Di Desa Tegal Giri Kecamatan Nogosari Kabupaten Boyolali - Mey Liswati, Erna, Endang Nur Widyaningsih, S.ST.,M.Si,Med, Irma Budi Hapsari, S.SiT (2016)
Backgroun The nutritional status of children under five is influenced by factors of socio-economic conditions, such as mother's education, mother's occupation, number of children, knowledge and parenting mothers and parents' economic conditions as a whole. Objective To determine the relationship between maternal characteristics that in this case a characteristic of age, education, occupation, and maternal parity in Tegal Giri, District Nogosari Boyolali. Research Method Were collected through questionnaires completed by the mothers were then analyzed using bivariate and multivariate. Result shows that the highest maternal age at age <20 and> 35 years (51.2%), most of mother's education is continuing education (62.8%). Maternal employment status at most were mothers who work and spend time outside the home> 6 hours (51.2%). Most mothers parity is parity ≤ 4 children (53.5%). The results showed that there was no relationship between age and mothers with nutrition(p: 0.473), mother's occupation with malnutrition (p: 0.473), mother's education with infant nutritional (p: 0.276), parity mothers with infant nutritional status (0.065). Conclusion The results of research conducted in the village of Tegalgiri districts Nogosari Boyolali about maternal characteristics to do with the nutritional status of children under five by respondents as many as 43 mothers, it can be concluded that there is no significant relationship between maternal characteristics (maternal age, education level, occupation of mother, parity mother ) with the nutritional status of children).